KEARIFAN LOKAL BERTAJUK RELIGI DALAM MITE GUNUNG TIDAR: KAJIAN ANTROPOLOGI SASTRA - Naililhaq, Fikha Nada (Jurnal Pendidikan Bahasa dan Sastra, 2020)
The Myth of Tidar Mountain is one of oral literature that flourishing around people of Magelang, Middle Java. This research aimes to describe religiosity in The Myth of Tidar Mountain with review of literary anthropology. The data source of this research came from myth that flourishing around the people. The data collecting method was done by two phase which is library research and continued with field research. Descriptive analytic method was used to analyzed the data that have been collected. The result of this research shows the correlation between religion and local people culture, especially Javanese culture. The correlation of both is reflected in Syababiyah tradition, Ruqyah, Correlation between Kyai Semar in Myth of Tidar Mountain with Semar in puppet show, and symbol or culture sites in Tidar Mountain.